Analysis Of The Basic Water Tariff Accounting System At The Regional Water Company (PDAM) Of Soppeng Regency - Nur Achriaty Achmar; Andi Muhammad Nurul Afdhal; Nur Fauziyah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2026)
The determination of basic water tariffs plays an important role in PDAM financial management because it affects the company's revenue and the quality of service provided to customers. The accounting system is used as a tool to calculate and record the cost components that are used as a reference in determining water tariffs. This study aims to examine the application of the accounting system in the process of determining basic water tariffs at PDAM Soppeng Regency. This study uses a descriptive quantitative approach because it presents basic water tariff calculations based on cost and water volume data obtained from PDAM Soppeng Regency. In addition, this approach is enriched with qualitative elements through interviews and observations of the tariff setting process and the application of accounting systems at PDAM Soppeng Regency. Based on the results of the study, it is known that the accounting system used contains important elements such as operational costs, maintenance, and various other types of expenses. However, several obstacles were still found, such as cost recording that was not entirely accurate and a lack of transparency in the tariff setting process to the public. Therefore, a system evaluation and periodic training for employees are needed so that the implementation of the accounting system at PDAM can run more optimally and in accordance with regulations